Beta-lactamase induction and cell wall metabolism in Gram-negative bacteria - Zeng, Ximin; Lin, Jun (Frontiers in Microbiology, 2013)
Production of beta-lactamases, the enzymes that degrade beta-lactam antibiotics, is the most widespread and threatening mechanism of antibiotic resistance. In the past, extensive research has focused on the structure, function, and ecology of beta-lactamases while limited efforts were placed on the regulatory mechanisms of beta-lactamases. Recently, increasing evidence demonstrate a direct link between beta-lactamase induction and cell wall metabolism in Gram-negative bacteria. Specifically, expression of beta-lactamase could be induced by the liberated murein fragments, such as muropeptides. This article summarizes current knowledge on cell wall metabolism, beta-lactam, and beta lactamases. In particular, we comprehensively reviewed recent studies on the beta-lactamase induction by muropeptides via two major molecular mechanisms (the AmpG-AmpR-AmpC pathway and BlrAB-like two-component regulatory system) in Gram-negative bacteria. The signaling pathways for beta-lactamase induction offer a broad array of promising targets for the discovery of new antibacterial drugs used for combination therapies. Therefore, to develop effective mitigation strategies against the widespread beta-lactam resistance, examination of the molecular basis of beta-lactamase induction by cell wall fragment is highly warranted.